Clinical and Functional Outcomes of Anterior Cruciate Ligament Reconstruction at a Minimum of 2 Years Using Adjustable Suspensory Fixation in Both the Femur and Tibia: A Prospective Study. Issue 10 (17th October 2018) - Colombet, Philippe; Saffarini, Mo; Bouguennec, Nicolas
Background: The success of anterior cruciate ligament (ACL) reconstruction requires reliable and rigid graft fixation. Cortical suspensory fixation (CSF) devices have become an acceptable alternative to interference screws for soft tissue ACL grafts. However, CSF devices have been reported to be associated with tunnel widening and increased postoperative anterior laxity compared with interference screw fixation. Adjustable CSF devices were introduced to avoid these problems but have been associated with graft lengthening and inconsistent outcomes. Purpose: To (1) report the side-to-side difference (SSD) in anterior laxity at 150 N, clinical scores, and failure rates 2 years after ACL reconstruction with 4-strand semitendinosus autografts using an adjustable CSF device and (2) determine the preoperative factors associated with clinical outcomes. Study Design: Case-control study; Level of evidence, 3. Methods: A total of 131 patients who had undergone primary ACL reconstruction, performed with 4-strand semitendinosus grafts that were secured using Pullup adjustable-length CSF devices with femoral and tibial fixation techniques, were prospectively enrolled in this study; 34 patients were excluded because of contralateral instability or ipsilateral knee injuries that required additional surgery. This left a cohort of 97 patients who were evaluated preoperatively and at 6, 12, and 24 months. The evaluation consisted of measuring the SSD in anterior laxity and patient-reported outcome scores (International Knee Documentation Committee [IKDC] and Lysholm scores). Regression analyses were performed to determine associations between these outcomes and 9 preoperative variables. Results: Only 2 patients could not be reached, 2 could not be evaluated because of contralateral ACL tears, and 2 had graft failure. At 2-year follow-up, the remaining 91 patients had a mean SSD in anterior laxity of 0.8 ± 1.8 mm (range, –4.2 to 5.3 mm), mean IKDC score of 87.6 ± 10.6 (range, 43.7-100.0), and mean Lysholm score of 90.8 ± 9.3 (range, 56.0-100.0). At final follow-up, compared with knees with partial ruptures, those with complete ruptures had equivalent laxity ( P = .266) and Lysholm scores ( P = .352) but lower IKDC scores ( P = .009). Multivariable regression revealed that the IKDC score decreased with increased preoperative laxity (β = –1.35 [95% CI, –2.48 to –0.23]; P = .019). Conclusion: The novel adjustable-length CSF device produced satisfactory anterior laxity and clinical outcomes, with a failure rate of 2.1%, which compare favorably with those reported for nonadjustable CSF devices.